Induced mutagenesis in creating genetic variability for seed yield and Alternaria leaf blight resistance in sunflower (Helianthus annus) - K. Sujatha; H.L. Nadaf; N. Srinivasa (Annals of Agricultural Research, 2023)
The successful use of plant breeding for improving desirable traits requires the existence of genetic variability for these traits. Induced mutations are often used to create new genetic variability within a plant species. The objective of this study was to provide new genetic variability that can be exploited for improvement of important agronomic and Alternaria leaf blight resistance traits in sunflower production. The seeds of TX16-R sunflower lines from the Directorate of Oilseed Research, Hyderabad was irradiated with gamma rays (γ) and treated in an ethylmethane sulphonate (ems) solution. The manifestation of mutations was mostly expressed in the M2 mutants were selected. Induced mutagenesis of TX-16R with gamma rays at two doses (200 Gy and 250 Gy) and with chemical mutagen EMS with two concentrations (0.015 mols/dm3 and 0.020 mols/dm3 ) was attempted to improve TX-16R for resistance to Alternaria leaf blight and agronomical traits. Gamma rays treatment at 250 Gy resulted in higher mortality and plants did not survive till the maturity. M1 generation was raised along with control. In M2 generation, more variability for resistance to blight and agronomic traits was seen in populations derived from EMS 0.020 mols/ dm3 treatment compared to 200 Gy (gamma rays) and EMS treatment at 0.015 mols/dm3 concentration and among three M2 population 200 Gy treatment has given higher frequency of highly resistant plants compare to 0.020 mols/dm3 and 0.015 mols/dm3 EMS treatment indicating that 200 Gy treatment is more desirable for getting highly resistant plants for Alternaria disease reaction.